PENGARUH PEMAHAMAN WAJIB PAJAK, KEMUDAHAN MEMBAYAR PAJAK, DAN PERUBAHAN TARIFPP NO. 46 TAHUN 2013 TERHADAPKEPATUHAN WAJIB PAJAK UMKM DI KOTA PEKANBARU - Nayoan, Nova; Hariyani, Eka; ', Hardi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect caused by the variable understanding of tax payer, ease of paying tax, and change in tariff pp no. 46 year 2013 for tax payer compliance of SMEs.This study uses convenience sampling with 86 samples from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows.Results of simultaneous regression test (Test F) showed that all independent variables had simultaneous influence on variable tax payer compliance of SMEs. Partial regression test (T test) showed that the variables understanding of tax payer, Ease of paying tax, and change in tariff pp no. 46 year 2013 had a significant effect on tax compliance SMEs. The magnitude of the effect posed (Adjusted R2) by these three variables together for the dependent variable is 41.7%, while the remaining 58.3% is influenced by other factors not examined in this study.Keywords: understanding, ease, tariff and tax compliance